2017
DOI: 10.18520/cs/v112/i02/267-278
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Inundation Research:An overview of the Process

Abstract: Coastal inundation is the flooding of coastal zone resulting from increased river discharge, spring tides, severe storms, or generation of powerful waves from tectonic activity (tsunami). This article discusses the critical factors that contribute to coastal inundation. Among the probable factors that cause coastal flooding and destruction, storm surge is the most frequent, and hence this article provides a detailed evaluation of the progress made in storm inundation research. Recent advances in coastal inunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 59 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…From the literature review, it is evident that most of the storm surge studies carried out for the Indian coast used stand-alone models (Rao et al, 2013a;Bhaskaran et al, 2014;Gayathri et al, 2015Gayathri et al, , 2016Dhana Lakshmi et al, 2017). A comprehensive review on the coastal inundation research and an overview of the processes for the Indian coast was reported by Gayathri et al (2017). One can find very few studies reported using a coupled model (ADCIRC with SWAN) for the Indian seas (Bhaskaran et al, 2013;Murty et al, 2014Murty et al, , 2016Poulose et al, 2017) for extreme weather events.…”
mentioning
confidence: 99%
“…From the literature review, it is evident that most of the storm surge studies carried out for the Indian coast used stand-alone models (Rao et al, 2013a;Bhaskaran et al, 2014;Gayathri et al, 2015Gayathri et al, , 2016Dhana Lakshmi et al, 2017). A comprehensive review on the coastal inundation research and an overview of the processes for the Indian coast was reported by Gayathri et al (2017). One can find very few studies reported using a coupled model (ADCIRC with SWAN) for the Indian seas (Bhaskaran et al, 2013;Murty et al, 2014Murty et al, , 2016Poulose et al, 2017) for extreme weather events.…”
mentioning
confidence: 99%
“…Coastal ooding occurs when the sea level at the coast episodically rises above the normal range of the tides (Gayathri et al 2017;Flick et al 2012). MHHW is commonly used as a reference to determine the threshold of coastal ooding.…”
Section: Mapping Potential Coastal Floodingmentioning
confidence: 99%
“…The coastal zone faces a variety of threats from severe storms such as tropical cyclones. Coastal ooding can result from several compounding factors, including river discharge, abnormally high astronomical tides such as spring tides, wind-induced storm tides/surges, and ocean surface wave run-up (Gayathri et al 2017). In tropical storms and hurricanes, storm surges and river ooding are the main factors ).…”
Section: Introductionmentioning
confidence: 99%